Transnational Corporate Interests in International Biosafety Negotiations - Jennifer Clapp (The International Politics of Genetically Modified Food: Diplomacy, Trade and Law, 2007)
Genetically modified food is at the heart of a new global conflict over how to govern risky technologies in an era of globalization. This timely collection brings together experts from the fields of IR, environmental studies, trade and law to examine the sources of international friction and to explore the prospects for international co-operation.